Mitochondrial Reactive Oxygen Species and Mitophagy: A Complex and Nuanced Relationship - Schofield, James H; Schafer, Zachary T (Antioxidants & redox signaling, 2021)
Mitochondria represent a major source of intracellular reactive oxygen species (ROS) generation. This is often a consequence of oxidative phosphorylation, which can produce ROS as a result of leakage from the electron transport chain. In addition, quality control mechanisms exist to protect cells from cytotoxic ROS production. One such mechanism is selective autophagic degradation of ROS-producing mitochondria, termed mitophagy, that ultimately results in elimination of mitochondria in the lysosome. However, while the relationship between mitophagy and ROS production is clearly interwoven, it is yet to be fully untangled. In some circumstances, mitochondrial ROS (mtROS) are elevated as a consequence of mitophagy induction. In this review, we discuss mtROS generation and their detrimental effects on cellular viability. In addition, we consider the cellular defense mechanisms that the eukaryotic cell uses to abrogate superfluous oxidative stress. In particular, we delve into the prominent mechanisms governing mitophagy induction that bear on oxidative stress. Finally, we examine the pathological conditions associated with defective mitophagy, where additional research may help to facilitate understanding.